2021
DOI: 10.1002/minf.202060084
|View full text |Cite
|
Sign up to set email alerts
|

ET‐score: Improving Protein‐ligand Binding Affinity Prediction Based on Distance‐weighted Interatomic Contact Features Using Extremely Randomized Trees Algorithm

Abstract: The molecular docking simulation is a key computational tool in modern drug discovery research that its predictive performance strongly depends on the employed scoring functions. Many recent studies have shown that the application of machine learning algorithms in the development of scoring functions has led to a significant improvement in docking performance. In this work, we introduce a new machine learning (ML) based scoring function called ET-Score, which employs the distanceweighted interatomic contacts b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Recently, customized protein–ligand interaction features became popular in scoring function development, such as ET-score (2021) and ECIF-GBT (2021) [ 104 , 106 ]. ET-score employed protein–ligand interaction features defined by distance-weighted interatomic contacts between atom type pairs of the protein and ligand.…”
Section: Machine-learning Scoring Functionmentioning
confidence: 99%
“…Recently, customized protein–ligand interaction features became popular in scoring function development, such as ET-score (2021) and ECIF-GBT (2021) [ 104 , 106 ]. ET-score employed protein–ligand interaction features defined by distance-weighted interatomic contacts between atom type pairs of the protein and ligand.…”
Section: Machine-learning Scoring Functionmentioning
confidence: 99%
“…As mentioned before, after excluding the core set, the refined set 2016, the composition of the refined and the general sets 2016, and the same composition for 2019 are used as the training sets. The distance‐weighted interatomic contact featurization method was applied to protein‐ligand complexes to generate a numerical representation for them [24]. RF, ET, and GBT were adopted as fast and standard learning algorithms to discern hidden patterns in the training data.…”
Section: Resultsmentioning
confidence: 99%
“…Distances with magnitude below the predefined cutoff ( d cutoff ) are weighted by an inverse power of a natural number ( n ) and sum together. In our previous work, we demonstrated that 12 A˙ ${\dot{A}}$ and 2 are appropriate choices for d cutoff and n , respectively [24]. The mentioned algorithm is repeated iteratively for all possible atom types pairs, and a feature vector with 400 dimensions as a representation of a protein‐ligand complex is produced [24]: X=XH,Hp,XH,Cp,,XI,Ih $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr \vec{X}=\left\{{X}_{H,{H}_{p}},{X}_{H,{C}_{p}},\dots, {X}_{I,{I}_{h}}\right\}\hfill\cr}}$ Xi,j=k=1Kjl=1Li1dlk2 $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {X}_{i,j}=\sum _{k=1}^{{K}_{j}}\sum _{l=1}^{{L}_{i}}{{1}\over{{d}_{lk}^{2}}}\hfill\cr}}$ …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the establishment of an in‐silico molecular design approach is still required [2–5] . Compared to ligand‐based drug design (LBDD), structure‐based drug design (SBDD), which is closely related to this study, is significantly advantageous in terms of identifying active compounds with novel molecular frameworks and different chemical classes [6,7] . Currently, many clinical drugs, including kinase inhibitors, such as erdafitinib, pexidartinib, and vemurafenib, have been developed through SBDD, [8] which has emerged as an effective approach for drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Compared to ligand-based drug design (LBDD), structure-based drug design (SBDD), which is closely related to this study, is significantly advantageous in terms of identifying active compounds with novel molecular frameworks and different chemical classes. [6,7] Currently, many clinical drugs, including kinase inhibitors, such as erdafitinib, pexidartinib, and vemurafenib, have been developed through SBDD, [8] which has emerged as an effective approach for drug discovery. However, one of the challenges associated with this approach is the difficulty in obtaining accurate ligandbinding poses.…”
Section: Introductionmentioning
confidence: 99%